Aquacel Surgical Dressing after Thigh Lift: A Case–Control Study. Issue 9 (September 2016) - Bocchiotti, Maria A.; Baglioni, Elisabetta A.; Spaziante, Luca; Frenello, Ambra; Ruka, Erind
Abstract : Background: The postoperative dressing in patients undergoing thigh lift is often difficult, not very resistant to movement, and uncomfortable for the patient, and often exposes surgical site to infection, maceration, or delay in wound healing. Methods: We included 40 patients in a case–control crossover study with no period effects, who were treated both by Aquacel Surgical and a traditional wound dressing. Surveys with a 10-point scale evaluation were used to assess nontraumatic removal level, ease of application, adhesion, and strength of the 2 treatments. We reported the number of days necessary for wound healing, the number of infection cases, and wound-related complications. Costs of the 2 medications were also considered. Ten days after surgery, patients answered a questionnaire with 6 multiple-choice questions to assess comfort, pain at dressing change, pruritus, strength, and number of dressing changes. Results: Compared with controls, surveys revealed Aquacel Surgical to be less traumatic to remove, easier to apply, and to be more adherent and stronger. Significant acceleration of the wound healing was also evident with Aquacel Surgical compared with the traditional dressing. Nonsignificant differences were reported about the risk of infection and wound-related complications between the 2 treatments. A statistical analysis of costs revealed that Aquacel Surgical is significantly more expensive than the traditional medication. Conclusion: We recommend the use of Aquacel Surgical in all the surgery procedures where the risk of wound dehiscence and maceration is high.